Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.
7/15:(1/2-9/10xX)-1/6=13/6
=>7/15:(1/2-9/10xX)=13/6+1/6
=>7/16:(1/2-9/10xX)=7/3
=>1/2-9/10xX=7/16:7/3
=>1/2-9/10xX=3/16
=>9/10xX=1/2-3/16
=>9/10xX=5/16
=>X=5/16:9/10
=>X=25/72
a. ( x - 1/2 ) x 5/3= 7/4 - 1/2
(x -1/2 ) x 5/3 = 5/4
x - 1/2 = 5/4 : 5/3
x - 1/2 = 3/4
x = 3/4 + 1/2
x = 5/4
b . 6/13 : ( 1/2 + x ) = 15/39
1/2 + x = 6/13- 15/39
1/2 + x = 1/13
x = 1/13 - 1/2
x = -11/26
c. 16/3 : (1/2+ x ) = 15/39
1/2 + x = 16/3 - 15/69
1/2 + x = 353/69
x = 353/69 - 1/2
x = 637/138
a: Sửa đề; \(A=\dfrac{7.2:2\cdot28.6+1.43\cdot2\cdot64}{1+3+5+7+...+49-339}\)
\(=\dfrac{3.6\cdot28.6+2.86\cdot64}{1+3+5+...+49-339}\)
\(=\dfrac{2.86\left(64+36\right)}{25^2-339}=\dfrac{286}{286}=1\)
b: =>2(x+7/8)=6*13/4=78/4=39/2
=>x+7/8=39/4
=>x=71/8
1, 2x - 35 = 15
2x = 15 + 35
2x = 50
x = 50 : 2
x = 25.
2, 3x + 18 = 12
3x = 12 - 18
3x = -6
x = -6 : 3
x = -2.
3, / x - 1 / = 0
=> x \(\in\varnothing\).
4, -13 /x/ = - 26
/x/ = -26 : -13
=> \(\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)
Vậy x \(\in\){ 2 ; -2}.
5,4 - ( 27 - 3 ) = x - ( 13 - 4 )
4 - 24 = x - 9
-20 = x - 9
-x = 9 + 20
-x = 29
x = -29.
6, 47 - ( x + 15 ) = 21
47 - x - 15 = 21
-x - 15 = 21 - 47
-x - 15 = -26
-x = -26 + 15
-x = - 11
x = 11.
7, -5 -( 24 - x) = - 11
-5 - 24 + x = -11
-24 + x = -11 + 5
-24 + x = -6
x = -6 + 24
x = 18.
8, 6 - /x/ = 2
/x/ = 6 - 2
\(\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)
Vậy x \(\in\left\{3;-3\right\}.\)
9, 6 + /x/ = 2
/x/ = 2 - 6
=> x = -4.
2x - 35 = 15
=> 2x = 15 + 35
=> x = 50 : 2
=> x = 25
3x + 18 = 12
=> 3x = 12 - 18
=> x = ( -6 ) : 3
=> x = -2
| x - 1 | = 0
=> x - 1 = 0
=> x = 0 + 1
=> x = 1
-13 * | x | = -26
=> | x | = -26 : ( -13 )
=> | x | = 2
\(\frac{315}{316}\cdot\frac{316}{314}\cdot\frac{316}{315}\cdot\frac{317}{313}=\frac{315.316.316.317}{316.314.315.313}=\frac{1.1.316.317}{1.314.1.313}=\frac{100172}{98282}\)
Ta có : \(\frac{3}{2}\times\frac{4}{5}\times\frac{2}{3}\)
\(=\frac{3}{2}\times\frac{2}{3}\times\frac{4}{5}=1\times\frac{4}{5}\)
\(=\frac{4}{5}\)
\(\dfrac{13}{6}:x=2-\dfrac{2}{5}\)
\(\dfrac{13}{6}:x=\dfrac{10}{5}-\dfrac{2}{5}\)
\(\dfrac{13}{6}:x=\dfrac{8}{5}\)
\(x=\dfrac{13}{6}:\dfrac{8}{5}\)
\(x=\dfrac{13}{6}x\dfrac{5}{8}\)
\(x=\dfrac{65}{48}\)